Salvianolic acid B attenuates renal interstitial fibrosis in rats with unilateral ureteral obstruction via Nrf2-Gpx4 pathway-mediated ferroptosis - SUN Yuanbo; SONG Yanran; WANG Shiqi; SUN Lixin; LI Guiqin (Di-san junyi daxue xuebao, 2022)
Objective To determine the improving effect of salvianolic acid B on renal interstitial fibrosis (RIF) of rats with unilateral ureteral obstruction (UUO) based on ferroptosis mediated by nuclear factor erythroid 2-related factor 2 (Nrf2)-glutathione peroxidase 4 (Gpx4) pathway. Methods A total of 40 rats were divided into sham operation group, model group, salvianolic acid B group, and salvianolic acid B+Nrf2 inhibitor group, with 10 rats in each group. UUO model was established in the latter 3 groups, and those of the sham operation group received the same operation except for not ligating and cutting the ureter. Salvianolic acid B of 100 mg·kg-1·d-1 and Nrf2 inhibitor ML385 of 30 mg·kg-1·d-1 were intragastrically administered to the corresponding groups, and sterile normal saline of equal volume was given to the sham operation group and model group, for 9 consecutive days. Hematoxylin-eosin (HE) staining and Masson staining were used to detect the morphology and fibrosis in renal tissues. The contents of Fe2+, maleicdialdehyde (MDA) and activity of superoxide dismutase (SOD) in renal tissues were detected with corresponding kits. Quantitative real-time PCR (RT-qPCR) and Western blotting were used to detect the mRNA and protein levels of Collagen-Ⅰ (CoL-Ⅰ), Collagen-Ⅲ (CoL-Ⅲ), Nrf2, and Gpx4 in the renal tissues. Results Compared with the sham operation group, the contents of Fe2+ and MDA and the mRNA and protein levels of CoL-Ⅰ and CoL-Ⅲ in the renal tissues were increased (P < 0.05), and the serum SOD activity and the mRNA and protein levels of Nrf2 were decreased (P < 0.05) in the model group. While the contents of Fe2+ and MDA and the mRNA and protein levels of CoL-Ⅰ and CoL-Ⅲ were decreased (P < 0.05), and the SOD activity and the levels of Nrf2 and Gpx4 were increased (P < 0.05) in the salvianolic acid B group than the model group. The treatment of salvianolic acid B+Nrf2 inhibitor increased the contents of Fe2+ and MDA and the mRNA and protein levels of CoL-Ⅰ and CoL-Ⅲ (P < 0.05), and reduced the SOD activity and the levels of Nrf2 and Gpx4 (P < 0.05) when compared with the salvianolic acid B group. Conclusion Salvianolic acid B activates the Nrf2-Gpx4 pathway and then inhibits ferroptosis to relieve RIF in UUO rats.